Examining effects of parent warmth and control on internalizing behavior clusters from age 8 to 12 in 12 cultural groups in nine countries - W. Andrew Rothenberg (2020)
© 2019 Association for Child and Adolescent Mental Health Background: Studies of U.S. and European samples demonstrate that parental warmth and behavioral control predict child internalizing behaviors and vice versa. However, these patterns have not been researched in other cultures. This study investigates associations between parent warmth and control and three child-reported internalizing behavior clusters to examine this question. Methods: Data from 12 cultural groups in 9 countries were used to investigate prospective bidirectional associations between parental warmth and control, and three child-reported internalizing behavior types: withdrawn/depressed, anxious/depressed, and somatic problems. Multiple-group structural equation modeling was used to analyze associations in children followed from ages 8 to 12. Results: Parent warmth and control effects were most pervasive on child-reported withdrawn/depressed problems, somewhat pervasive on anxious/depressed problems and least pervasive on somatic problems. Additionally, parental warmth, as opposed to control, was more consistently associated with child-reported internalizing problems across behavior clusters. Child internalizing behavior effects on parental warmth and control appeared ubiquitously across cultures, and behaviors, but were limited to ages 8–10. Most effects were pancultural, but culture-specific effects emerged at ages 9–10 involving the associations between parent warmth and withdrawn/depressed and somatic behaviors. Conclusions: Effects of parent warmth and control appear stronger on some types of child-reported internalizing behaviors. Associations are especially strong with regard to parental warmth across cultures, and culture-specific effects may be accounted for by cultural normativeness of parent warmth and child-reported somatic symptoms. Child internalizing behavior effects on subsequent parenting are common across cultures.